Effects of Arrests and Incarceration on Informal Social Control in Baltimore, Maryland, Neighborhoods, 1980-1994 - Lynch, James P. ([Verlag nicht ermittelbar], 2003)
This study examined the effects of police arrest policies and incarceration policies on communities in 30 neighborhoods in Baltimore. Specifically, the study addressed the question of whether aggressive arrest and incarceration policies negatively impacted social organization and thereby reduced the willingness of area residents to engage in informal social control, or collective efficacy. CRIME CHANGES IN BALTIMORE, 1970-1994 (ICPSR 2352) provided aggregate community-level data on demographics, socioeconomic attributes, and crime rates as well as data from interviews with residents about community attachment, cohesiveness, participation, satisfaction, and experiences with crime and self-protection. Incident-level offense and arrest data for 1987 and 1992 were obtained from the Baltimore Police Department. The Maryland Department of Public Safety and Corrections provided data on all of the admissions to and releases from prisons in neighborhoods in Baltimore City and Baltimore County for 1987, 1992, and 1994.